EARLY SOCIAL PROBLEM SOLVING ABILITY OF ELEMENTARY SCHOOL STUDENTS IN BARAT BANDUNG DISTRICT - Nurdiansyah Deni; Nano Nurdiansah; Mubiar Agustin (Sekolah Pascasarjana UPI, 2022)
This research is motivated by the tendency of the low social problem solving ability of elementary school students. Problem solving ability is not accustomed to elementary school students, students are never directed and invited by teachers to solve simple social problems. So it is important for children to have social problem solving skills as a provision for students in dealing with problems and making it easier to solve any problems they face. This study aims to determine the initial ability to solve social problems of elementary school students. The method used in this study is a qualitative descriptive method. Research participants involved 37 students of class Va in one of the public elementary schools in Cipongkor District, West Bandung Regency on social issues. The instruments used in data collection were learning observation sheets, test questions, and SPSI-R short form questionnaires. The research data were analyzed qualitatively through scoring and percentages based on the emergence of aspects and indicators of social problem solving. The results showed that the average percentage of students' social problem-solving ability indicators in the low category based on the results of learning observations was 37.5%, based on the results of the essay test, it was in the medium category, 41.95%, and based on the SPSI-R short form questionnaire, it showed the category low with a high score of 70.54 on the Impulsivity/Carelessness Style (ICS) dimension. Thus, the researcher can conclude that the initial ability of students to solve social problems in one of the public elementary schools in West Bandung Regency is in the relatively low category.